Blended Mode of Learning is the Way Forward in the Post Pandemic Era - Anchal Sharma (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2021)
COVID-19 Pandemic has caused many abrupt and profound changes in the Education Sector around the world. Due to the school closures, India has also witnessed a large number of students suffering from huge learning gaps. With the current priority of reopening the schools and bringing the students back to the classrooms in a safe manner, blended learning is seen as a fundamental part of the future of education. Blended learning is a way of learning combining traditional and modern learning models, with the help of digital learning platforms and tools. The power of blended learning methods lies in their ability to improve the learning experience for both the teachers and the students. Despite various efforts by the government and independent organizations, making learning possible for all learners has been a challenging journey. It has contributed to the increase in resourcefulness, dedication, and creativity for many teachers, families, and students who are collaboratively building remarkable learning experiences during the school closures. Also, it has disclosed many weaknesses and vulnerabilities of the system in making the dream of digital India possible. With the utmost priority to bring back children safely to the schools, various studies see technology playing a crucial part in the process. This allows the scope of providing more opportunities for collaboration, increased access to learning, advanced systems for tracking learning levels, and preparing learners for a tech-oriented future. A blended mode of learning is seen as a balanced way out to bring our children safely to the schools and optimize ICT tools and platforms to accelerate the learning process. Open educational resources must be prioritized, public education cannot be dependent on digital platforms provided by private companies[1]. This will require all the stakeholders on the national level, state level, civil societies, teachers, students, and parents all collectively mobilizing these efforts. Thus, making it important to ensure that any digital transition is not just an effort pushed by technology companies but the teachers, students, governments, civil society representatives and privacy advocates are also represented and shape these transformations.
Keywords: 330